2017
DOI: 10.3832/ifor2093-010
|View full text |Cite
|
Sign up to set email alerts
|

Integration of tree allometry rules to treetops detection and tree crowns delineation using airborne lidar data

Abstract: Airborne laser scanning (ALS) has recently gained increasing attention in forestry, as ALS data may facilitate the efficient assessment of forest inventory attributes and ecological indicators related to forest stand structure. This paper presents a novel workflow for individual tree detection and tree crown delineation using ALS data. The developed point-based approach included several tree allometry rules on permissible tree heights and crown dimensions to increase the likelihood of detecting the actual tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
(41 reference statements)
1
14
0
1
Order By: Relevance
“…Vauhkonen et al [42] stated that the accuracy of tree detection in Scandinavia and Central Europe forests should be around 70%. Regarding algorithms used in this study, the accuracy of tree detection is found within the interval of 52%-84% according to the results from this study ( Table 2) and previous research for the same study area [26,27]. However, the commission rate of the raster-based method may exceed 45%, while the commission rate of multisource-based method is usually within 8%.…”
Section: Stand Density Indexsupporting
confidence: 63%
See 1 more Smart Citation
“…Vauhkonen et al [42] stated that the accuracy of tree detection in Scandinavia and Central Europe forests should be around 70%. Regarding algorithms used in this study, the accuracy of tree detection is found within the interval of 52%-84% according to the results from this study ( Table 2) and previous research for the same study area [26,27]. However, the commission rate of the raster-based method may exceed 45%, while the commission rate of multisource-based method is usually within 8%.…”
Section: Stand Density Indexsupporting
confidence: 63%
“…Finally, the outputs of all procedures were exported to point and polygon vector files in an ESRI shapefile format. All details of the algorithm are listed in the study of Sačkov et al [26].…”
Section: Individual Tree and Tree Height Detectionmentioning
confidence: 99%
“…The laser data had an average density of laser hits of 4.3 pt/m 2 . In further processing, the point clouds were classified in accordance with the American Society for Photogrammetry and Remote Sensing classes, and noise points were removed using reFLex software [25].…”
Section: Ground Reference Datamentioning
confidence: 99%
“…Because of the increased spatial resolution of UAV LiDAR data, some studies, to improve segmentation accuracy, segmented individual trees directly from point clouds. The existing point-based clustering methods (such as region growing [17], k-means clustering [26], normalized cut [28], and mean shift [29,30]) have been widely used for individual tree segmentation in terms of 3D data characteristics, geometric structures, and height variation of trees [31][32][33]. Compared with other clustering methods, mean shift does not require seed points or number of clusters before clustering.…”
Section: Introductionmentioning
confidence: 99%